THE CONCEPT OF TAZKIYATUN AN-NAFS: GUIDANCE IN HANDLING DRUG USERS - Maryatul Kibtiyah; Dina Alhida Sa'id; Elsa Dwi Mahfiroh; Rizka Lutfiana Zakiyatun Nisa (AL-TAZKIAH, 2026)
Narcotics (NAPZA) remains a major problem in Indonesia, causing physical, psychological, and spiritual damage to individuals. Therefore, treatment efforts are needed that are not only medical and legal but also address religious aspects through an integrated approach. This study aims to examine efforts to treat drug users through the tazkiyatun an-nafs counseling approach. This study uses a descriptive method and content analysis of the literature to provide an overview of the concept and application of tazkiyatun an-nafs in Islamic guidance. Data sources were obtained from various published media relevant to this study. This study is directed at developing a pious personality, namely a person with strong faith, free from heart disease, and noble morals, able to live life with a good attitude to achieve happiness in this world and the hereafter. The results of the study indicate that guidance through the stages of takhalli, tahalli, and tajalli is an important means of purifying the soul, in line with the concept of tazkiyatun an-nafs. This study recommends the application of the tazkiyatun an-nafs approach in dealing with drug users as an effort to foster spiritual development and character building to become better, more pious individuals.